John Paul Stevens: An Independent Life - Barnhart, Bill (NORTHERN ILLINOIS UNIVERS, 2010)
This volume is a biography of John Paul Stevens (b. 1920). Stevens served as an Associate Justice of the Supreme Court of the United States from 1975 until his retirement in 2010. He was nominated by President Gerald Ford. Through family history and a look at his work on the bench, the authors profile the second longest serving Supreme Court justice of the modern era -- one who has proudly earned the title of the "Court's most prolific dissenter". They interviewed Stevens and an extraordinary number of Stevens's friends and family members, former clerks, current colleagues, politicians, and court watchers. They trace his early years as a Chicago lawyer, his appointment to the federal appeals bench in Chicago, and his ultimate nomination to the Supreme Court. They examine his best-known opinions, including his emotional dissents in Texas v. Johnson and Bush v. Gore, also tracing his growth as a molder of Court decisions